2017
DOI: 10.1002/etc.4021
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and dissipation of neonicotinoid residues in nectar and foliage of systemically treated woody landscape plants

Abstract: Systemic neonicotinoid insecticides used in urban arboriculture could pose a risk to bees and other pollinators foraging on treated plants. We measured uptake and dissipation of soil-applied imidacloprid and dinotefuran in nectar and leaves of 2 woody plant species, a broadleaf evergreen tree (Ilex × attenuata) and a deciduous shrub (Clethra alnifolia), to assess concentrations to which pollinators and pests might be exposed in landscape settings. Three application timings, autumn (postbloom), spring (prebloom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 46 publications
(77 reference statements)
0
24
0
Order By: Relevance
“…Since collection of these samples is resource intensive, it is critical to develop efficient and accurate extraction and quantification methods. Currently, sample preparation in combination with LC-MS/MS for neonicotinoid quantification in plant tissue and pollen has been limited to more intensive extraction methods with high-mass samples and longer LC-MS/MS runs [14,[16][17][18][19]22,23,30]. To address these limitations, we developed a single extraction and analytical method for multiple neonicotinoids from milkweed leaf tissue and pollen.…”
Section: Discussionmentioning
confidence: 99%
“…Since collection of these samples is resource intensive, it is critical to develop efficient and accurate extraction and quantification methods. Currently, sample preparation in combination with LC-MS/MS for neonicotinoid quantification in plant tissue and pollen has been limited to more intensive extraction methods with high-mass samples and longer LC-MS/MS runs [14,[16][17][18][19]22,23,30]. To address these limitations, we developed a single extraction and analytical method for multiple neonicotinoids from milkweed leaf tissue and pollen.…”
Section: Discussionmentioning
confidence: 99%
“…Risks of chemical insecticide use in urban landscape areas may include: (1) insecticide drift from foliar sprays [8], (2) leaching and runoff of insecticides into the water sources or drainage systems [9], (3) possibility of insecticide resistance development in the whitefly population due to prolonged use of the same chemical group [10,11], and (4) the negative impact on the non-target organisms, e.g. humans, domestic animals, natural enemies and pollinators [8,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the half-life is observed to be longer than that of other crops. Additionally, it has been reported that dinotefuran, which was treated with canola seeds, remained for a long time and exceeded the harvest season [24]. This suggests that even with the same pesticide, the residue period may vary based on the crop and the growing environment.…”
Section: Dissipation Pattern Of Test Pesticide In Fresh Persimmonmentioning
confidence: 99%